1995
DOI: 10.1002/hed.2880170609
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in levels of different protein kinase C isotypes and their influence on behavior of squamous cell carcinoma of the oral cavity: εPKC, a novel prognostic factor for relapse and survival

Abstract: These results suggest participation of some PKC isotypes (alpha, beta, gamma, and zeta) in the genesis and behavior (epsilon) of oral cancers. Levels of epsilon PKC could be used as prognostic marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…Although similar expression of PKCs (a, y, q, D, and~) in normal human keratinocytes was observed (16), different expression patterns have also been reported (17). There is limited data available about PKC expression in SCCHN, and the results are conflicting (18,19). Our study would suggest that the novel isoforms (y, q, and u) are highly expressed in SCCHN cell lines.…”
Section: Discussionsupporting
confidence: 48%
“…Although similar expression of PKCs (a, y, q, D, and~) in normal human keratinocytes was observed (16), different expression patterns have also been reported (17). There is limited data available about PKC expression in SCCHN, and the results are conflicting (18,19). Our study would suggest that the novel isoforms (y, q, and u) are highly expressed in SCCHN cell lines.…”
Section: Discussionsupporting
confidence: 48%
“…To date, there is only one publication of note focusing on the role of PKCs in HNSCC. In this study, PKCa, PKCh, PKCq, PKCg, and PKC~protein levels were shown to be elevated in the primary tumor tissue of oral cavity patients; however, only PKCq was found to be a prognostic marker in this small cohort of 29 patients, even better than the traditional gold standard of tumor-node-metastasis staging (11). Elevated PKCq was reported to be significantly associated with an increase in disease recurrence (P < 0.04) and a decrease in overall survival (P < 0.02).…”
Section: Resultsmentioning
confidence: 56%
“…Our laboratory reported that elevated PKCq is prognostic of lower overall and disease-free survival in patients with invasive breast cancer (10). Moreover, higher levels of PKCq were found to correlate with an increase in disease recurrence and a decrease in overall survival in HNSCC (11). In this study, we report that specific inhibition of PKCq is sufficient to dampen the invasive and motile phenotype of aggressive HNSCC.…”
Section: Introductionmentioning
confidence: 52%
“…PKC isoenzymes have been found to display variable expression profiles depending on specific cancer type. For example, PKCa and b has shown over-expressed in both high grade of prostate, gastrointestinal tract and head neck cancers (Koren et al, 2004;Lahn et al, 2004;Martinez-Gimeno et al, 1995). In contrast, hepatocellular and breast cancer display a downregulation of PKCa, and bladder cancer shows a down regulation of PKCb (Tsai et al, 2000;Kerfoot et al, 2004;Varga et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…As for PKC e and z, although their cellular function still obscure, their expressions have been reported in various cancers. PKCe has been shown upregulated in head neck, brain and prostate cancers (Xiao et al, 1994;Martinez-Gimeno et al, 1995;Sharif and Sharif, 1999;Koren et al, 2004), whereas downregulated in pancreatic cancer (Evans et al, 2003). PKCz have been shown upregulated in brain, liver and bladder cancers (Xiao et al, 1994;Tsai et al, 2000;Varga et al, 2004).…”
mentioning
confidence: 99%